Hubungan Abnormalitas Ekokardiografi terhadap Mortalitas Pasien Terkonfirmasi COVID-19 Derajat Berat dan Kritis di RSUPN Dr. Cipto Mangunkusumo - Santoso, Fidiaji Hiltono; Alwi, Idrus; Nasution, Sally A.; Rumende, Cleopas Martin (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. The mortality rate of COVID-19 patients in Indonesia is high with manifestations of cardiac complications. Echocardiographic evaluation can help identify cardiac functional and structural disorders associated with patient mortality. Therefore, this study aims to determine the relationship between echocardiographic abnormalities and mortality in severe and critical COVID-19 patients. Methods. A retrospective cohort study was conducted using medical record data of severe and critical COVID-19 patients at Dr. Cipto Mangunkusumo Hospital Jakarta during March 2020 to April 2021. Subjects were selected using total sampling. Descriptive analysis was performed, presenting descriptive tables, and bivariate analysis was conducted using the chi-square test. Results. Of the total 83 patients, 30 (36.1%) were classified as severe and 53 (63.9%) as critical. Most of the subjects were male, with 21 (70%) in the severe group and 33 (62.2%) in the critical group, with a median age of 55.5 (23-95) years for the severe group and 59 (23-83) years for the critical group. A total of 48 patients (57.8%) in this study died. The most common functional abnormality found on echocardiography was mPAP in 51 or 68%, and the most structural disturbance was left ventricular concentric remodelling in 48 or 58%. The chi-square analysis results of echocardiographic variables namely TAPSE with RR = 7.292, Right Ventricular Systolic Pressure (RVSP) 10.208, mean Pulmonary Artery Pressure (mPAP) 1.440, Pulmonary Acceleration Time (PAT) 2.357, and Right Atrial Pressure (RAP) 3.403 had a significant relationship with mortality. Meanwhile, LVEF, E/e’ and CO have no significant relationship. Based on the multivariate analysis, variables independently associated with mortality were RVSP and RAP. Conclusion. Echocardiographic abnormalities associated with mortality in severe and critical COVID-19 patients were TAPSE, RVSP, mPAP, PAT and RAP estimation.